Periacetabular quadruple osteotomy of the pelvis in older children: computed tomography scan analysis of acetabular retroversion and anterior overcoverage of the hip, preventing femoral acetabular impingement. Issue 3 (May 2018) - Jawish, Roger; Najdi, Hassan; Krayan, Ali
Abstract : The periacetabular quadruple osteotomy of the pelvis (QOP), with the osteotomy of ischial spine to release the sacrospinal ligament, is reserved for older children with low potential of remodeling. Different parameters were studied with computed tomography (CT) scan before (pre-OH) and after surgery (post-OH) and for nonoperated hip (NOH). The study determined an optimal method to avoid retroversion and excessive anterior coverage. Fifteen QOP were performed in 13 patients, ranging in age from 10 to 15 years. The morphology of pelvis was analyzed with a CT scan before the surgery and 2 years after. Pathologies were Legg–Calve–Perthes (seven hips) and dysplasia (eight hips). The two-dimensional exam measured the acetabular index, the coverage, and the version of the acetabulum. The three-dimensional images measured the frontal lateral inclinations of the lips and the sagittal anterior acetabular inclination. The mean anterior acetabular index was 50.4° (NOH), 56° (pre-OH), and 58.7° (post-OH). The posterior acetabular index was 48.5° (NOH), 52.2° (pre-OH), and 40° (post-OH). The anterior coverage angle was 37.1° in (pre-OH), 27.6° (post-OH), and 30.1° (NOH). The posterior coverage was 20.4° (pre-OH), 17.2° (post-OH), and 12.4° (NOH). The acetabular version was 2.1° (pre-OH), 8.3° (post-OH), and 2.5° (NOH). The anterolateral lip inclination was 50.3° (pre-OH), 35.3° (post-OH), and 43.8° (NOH). The posterolateral lip inclination was 56.7° (pre-OH), 43.7° (post-OH), and 55.8° (NOH). The anterior acetabular inclination was 21.3° (pre-OH), 15.6° (post-OH), and 18° (NOH). The QOP enabled significant range of coverage of the hip in adolescents in whom the potential of remodeling is very low. External rotation related to figure-of-four should be omitted, whereas the maneuver to be applied, preventing the anterior impingement and decrease of the posterior coverage, should be performed by placing the acetabular fragment below the iliac bone, with a lateral inclination in the frontal plane similar to a steering wheel movement. This maneuver preserves comparable morphology of the OH with NOH and avoids retroversion with the excessive anterior coverage responsible for pain and early osteoarthritis.